LOW NOISE ELECTRONICS MODULE FOR AVALANCHE PHOTODIODE SIGNAL READOUT - O. V. Dvornikov; V. A. Tchekhovski; V. L. Diatlov; N. N. Prokopenko (Приборы и методы измерений)
Schematic and design of electronics module for avalanche photodiode signal′s readout based on the pair of specialized analog ICs, are considered. Main specifications including input noise charge vs signal source capacity are presented.